Thermoelectric amplification of phonons in graphene - Dompreh, K.A.; Mensah, N.G.; Mensah, S.Y.; Fosuhene, S.K. (Физика низких температур, 2016)
Amplification of acoustic in-plane phonons due to an external temperature gradient (∇T) in single-layer graphene (SLG) was studied theoretically.